Estimation of Biophysical Parameters of Forage Cactus Under Different Agricultural Systems Through Vegetation Indices and Machine Learning Using RGB Images Acquired with Unmanned Aerial Vehicles - Silva, Gabriel Italo Novaes da; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Santos, Wagner Martins dos; Bezerra, Alan Cézar; Alba, Elisiane; Silva, Marcos Vinícius da; Silva, Jhon Lennon Bezerra da; Souza, Luciana Sandra Bastos de; Marinho, Gabriel Thales Barboza; Montenegro, Abelardo Antônio de Assunção; Silva, Thieres George Freire da (MDPI, 2024)
The objective of this study was to correlate the biophysical parameters of forage cactus with visible vegetation indices obtained by unmanned aerial vehicles (UAVs) and predict them with machine learning in different agricultural systems. Four experimental units were conducted. Units I and II had different plant spacings (0.10, 0.20, 0.30, 0.40, and 0.50 m) with East–West and North–South planting directions, respectively. Unit III had row spacings (1.00, 1.25, 1.50, and 1.75 m), and IV had cutting frequencies (6, 9, 12 + 6, and 18 months) with the clones “Orelha de Elefante Mexicana”, “Miúda”, and “IPA Sertânia”. Plant height and width, cladode area index, fresh and dry matter yield (FM and DM), dry matter content, and fifteen vegetation indices of the visible range were analyzed. The RGBVI and ExGR indices stood out for presenting greater correlations with FM and DM. The prediction analysis using the Random Forest algorithm, highlighting DM, which presented a mean absolute error of 1.39, 0.99, and 1.72 Mg ha−1 in experimental units I and II, III, and IV, respectively. The results showed potential in the application of machine learning with RGB images for predictive analysis of the biophysical parameters of forage cactus.
Keywords: automated procedures; ExGR; forage cactus; Random Forest; RGBVI; visible vegetation indices